Solar cell and preparation method thereof

By opening grooves on the battery substrate of the solar cell and performing metal paste sintering, the problem of difficulty in thinning the polysilicon layer in the prior art is solved, and the effect of reducing parasitic absorption and improving battery efficiency is achieved.

CN119451310APending Publication Date: 2025-02-14TRINA SOLAR (YANGZHOU) OPTOELECTRONICS CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411550428.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing preparation methods of solar cells are difficult to thin the polysilicon layer, resulting in a decrease in battery efficiency.

Method used

By opening a groove on the second side of the battery substrate, the groove extends into the polysilicon layer, the metal paste is printed and heated and sintered, so that the metal paste and the polysilicon layer are formed into ohmic contact. This method reduces the sintering temperature, controls the depth of the metal slurry corrosion of the polysilicon layer, and thins the polysilicon layer to reduce parasitic absorption.

Benefits of technology

It is realized that while ensuring good ohmic contact between the metal paste and the polysilicon layer, the sintering temperature and corrosion rate are reduced, the polysilicon layer is effectively thinned, and the efficiency of solar cells is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451310A_ABST
    Figure CN119451310A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solar cells, particularly provides a preparation method of a solar cell, and aims to solve the problem that a polycrystalline silicon layer is difficult to thin in an existing preparation method of the solar cell. In order to achieve the purpose, the preparation method of the solar cell comprises the steps that a tunneling oxide layer, a polycrystalline silicon layer and a second anti-reflection layer are sequentially formed on the second side of a substrate; forming a groove, wherein the groove extends into the second anti-reflection layer or the polycrystalline silicon layer from the surface of the second anti-reflection layer; printing metal slurry in the groove; and heating and sintering the metal slurry to enable the metal slurry and the polycrystalline silicon layer to form ohmic contact. In the heating and sintering process, the thickness of the second anti-reflection layer corroded by the metal slurry is small, the sintering temperature can be reduced on the premise that good ohmic contact is formed between the metal slurry and the polycrystalline silicon layer, the rate of corroding the polycrystalline silicon layer by the metal slurry is reduced, the depth of corroding the polycrystalline silicon layer by the metal slurry can be controlled, and the service life of the polycrystalline silicon layer is prolonged. Therefore, the polycrystalline silicon layer is thinned to reduce parasitic absorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of solar cells, and specifically provides a method for preparing a solar cell. Background Art

[0002] At present, with the continuous consumption of traditional energy, energy issues have become an important issue of global concern, and promoting the development of renewable energy has become the focus. Among them, solar energy has significant advantages such as cleanliness, safety, and abundant resources. It has gradually emerged and become the focus of research and development. After decades of development, photovoltaic power generation technology has also made remarkable progress.

[0003] Among them, TOPcon cell is a kind of solar cell. The efficiency of the cell has exceeded 26%, which has not yet reached the limit. There is still huge room for improvement in the efficiency of TOPcon cell (for example, in terms of improving the open circuit voltage and fill factor of the cell and reducing parasitic absorption).

[0004] TOPcon cells include a substrate, and a passivation layer, a polysilicon layer, and an anti-reflection layer are formed on the second side of the substrate in sequence. Then, a metal paste is printed on the anti-reflection layer by screen printing, and then sintered at high temperature to form a metal electrode. During the high-temperature sintering process, the metal paste will corrode the anti-reflection layer, thereby passing through the anti-reflection layer and forming an ohmic contact with the polysilicon layer. In TOPcon cells, the polysilicon layer will absorb part of the sunlight, resulting in parasitic absorption, which will reduce the efficiency of the cell.

[0005] The current design of TOPcon cells considers thinning the polysilicon layer to reduce parasitic absorption and thus improve cell efficiency. However, after the polysilicon layer is thinned, the high-temperature sintering process of the metal paste is difficult to control. If the sintering temperature is too high, the metal paste will corrode the polysilicon layer and damage the passivation layer, thereby reducing the open circuit voltage of the TOPcon cell; if the sintering temperature is too low, it will be difficult for the metal paste to completely corrode the anti-reflection layer and form a good ohmic contact with the polysilicon layer.

[0006] Therefore, there is an urgent need for a solar cell and a preparation method thereof to solve the problem that it is difficult to thin the polysilicon layer in the existing preparation method of solar cells. Summary of the invention

[0007] The present disclosure aims to solve the above technical problem, that is, to solve the problem that it is difficult to thin the polysilicon layer in the existing solar cell preparation method.

[0008] In a first aspect, the present disclosure provides a method for preparing a solar cell, comprising: providing a cell substrate, the cell substrate comprising a substrate and a tunneling oxide layer, a polysilicon layer, and a second anti-reflection layer formed in sequence on a second side of the substrate; opening a groove on the second side of the cell substrate, the groove extending from a surface of the second anti-reflection layer to inside the second anti-reflection layer or inside the polysilicon layer; printing a metal paste in the groove; heating and sintering the metal paste so that the metal paste forms an ohmic contact with the polysilicon layer and the bottom of the metal paste is located in the polysilicon layer.

[0009] In a specific implementation of the method for preparing the solar cell, the groove extends into the polysilicon layer, and the ratio of the thickness of the polysilicon layer region exposed by the groove to the thickness of the polysilicon layer is 50% to 66%.

[0010] In a specific implementation of the method for preparing the solar cell, the depth of the groove in the polysilicon layer is 15 nm to 35 nm; and / or the thickness of the polysilicon layer is 45 nm to 85 nm.

[0011] In a specific embodiment of the above-mentioned method for preparing a solar cell, the peak temperature of the heating sintering is 600°C to 700°C.

[0012] In a specific embodiment of the above-mentioned solar cell preparation method, the metal paste is silver paste, and the weight percentage of the silver paste is: 90% to 95% silver powder, 0.2% to 0.3% glass powder, 1% to 3% organic carrier and 0% to 1% inorganic additive.

[0013] In a specific implementation of the method for preparing the solar cell, after the metal paste is heated and sintered, the metal paste is subjected to laser-assisted sintering.

[0014] In a specific embodiment of the above-mentioned method for preparing the solar cell, the laser assisted sintering includes: applying a bias voltage of 10V to 40V between the metal slurry and the first side of the substrate; the wavelength of the scanning laser is 500nm to 1200nm, the scanning speed is 1000m / s to 70000m / s, and the scanning time is 0.5s to 1s.

[0015] In a specific implementation of the above-mentioned method for preparing a solar cell, the thickness of the polysilicon layer is 45 nm to 85 nm.

[0016] In a specific implementation of the method for preparing the solar cell, a doping layer, a passivation layer and a first anti-reflection layer are sequentially formed on the first side of the substrate.

[0017] In a specific embodiment of the above-mentioned solar cell preparation method, the polysilicon layer includes a first polysilicon layer of a first doping type and a second polysilicon layer of a second doping type, and the grooves are formed in the regions corresponding to the first polysilicon layer and the second polysilicon layer.

[0018] In a specific implementation of the above-mentioned method for preparing a solar cell, the groove is formed by laser etching; or, the groove is formed by wet etching or dry etching.

[0019] In a second aspect, the present disclosure provides a solar cell manufactured using the above-mentioned manufacturing method.

[0020] Compared with the prior art, the present invention has at least the following technical effects:

[0021] The present disclosure provides a method for preparing a solar cell, including: providing a cell substrate, the cell substrate including a substrate and a tunneling oxide layer, a polysilicon layer and a second anti-reflection layer formed in sequence on the second side of the substrate; opening a groove on the second side of the cell substrate, the groove extending from the surface of the second anti-reflection layer to the second anti-reflection layer or the polysilicon layer; printing a metal paste in the groove; heating and sintering the metal paste, the heating and sintering adopts heating and sintering, so that the metal paste forms an ohmic contact with the polysilicon layer and the bottom of the metal paste is located in the polysilicon layer. By opening the groove, during the heating and sintering process, the thickness of the second anti-reflection layer corroded by the metal paste is relatively thin, so that the sintering temperature can be reduced under the premise of ensuring that the metal paste forms a good ohmic contact with the polysilicon layer, so that the rate of the metal paste corroding the polysilicon layer is reduced, which helps to control the depth of the metal paste corroding the polysilicon layer, so as to reduce the parasitic absorption of the cell by thinning the polysilicon layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The preferred embodiments of the present disclosure are described below in conjunction with the accompanying drawings, in which:

[0023] Figure 1 A flow chart of the preparation of a solar cell provided by the present disclosure;

[0024] FIG. 2A to FIG. 2D A cross-sectional structure diagram of the first solar cell provided by the present disclosure during the preparation process;

[0025] Figure 2E A cross-sectional structural diagram of the first solar cell provided by the present disclosure;

[0026] FIG. 3A to FIG. 3E A cross-sectional structure diagram of the second solar cell provided by the present disclosure during the preparation process;

[0027] Figure 3F This is a cross-sectional structural diagram of a second solar cell provided by the present disclosure.

[0028] Description of reference numerals:

[0029] 1. Substrate; 11. Doping layer; 2. Tunneling oxide layer; 3. Polysilicon layer; 31. First polysilicon layer; 32. Second polysilicon layer; 33. Isolation region; 4. Passivation layer; 5. First anti-reflection layer; 6. Second anti-reflection layer; 71. First electrode; 72. Second electrode; 10. First groove; 20. Second groove. DETAILED DESCRIPTION

[0030] The preferred embodiments of the present disclosure are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present disclosure and are not intended to limit the protection scope of the present disclosure.

[0031] It should be noted that in the description of the present disclosure, the terms "upper", "lower", "left", "right", "inner", "outer" and the like indicating directions or positional relationships are based on the directions or positional relationships shown in the drawings, which are only for the convenience of description, and do not indicate or imply that the device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present disclosure. In addition, the terms "first" and "second" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0032] In order to solve the problem that it is difficult to maintain or improve the fill factor while increasing the open circuit voltage of solar cells, such as Figure 1 As shown, the present disclosure provides a method for preparing a solar cell, comprising: providing a cell substrate, the cell substrate comprising a substrate and a tunneling oxide layer, a polysilicon layer and a second anti-reflection layer formed in sequence on a second side of the substrate; opening a groove on the second side of the cell substrate, the groove extending from the surface of the second anti-reflection layer to the inside of the second anti-reflection layer or the polysilicon layer; printing metal paste in the groove; heating and sintering the metal paste so that the metal paste forms an ohmic contact with the polysilicon layer and the bottom of the metal paste is located in the polysilicon layer.

[0033] Embodiment 1

[0034] FIG. 2A to FIG. 2D This is a cross-sectional structural diagram of the first solar cell provided in the present disclosure during the preparation process. Figure 2E This is a cross-sectional structural diagram of the first solar cell provided by the present disclosure. In this embodiment, the solar cell is specifically a TOPcon cell.

[0035] The method for preparing a solar cell provided by the embodiment of the present disclosure is specifically as follows:

[0036] S1. Provide a substrate 1, which is of a first doping type. The substrate 1 has a first side surface and a second side surface opposite to the first side surface. The first side surface of the substrate 1 is a light-facing side, and the second side surface of the substrate 1 is a backlight side.

[0037] S2. Texturing is performed on the first side and the second side of the substrate 1 to form a pyramid-like structure on the first side and the second side of the substrate 1, thereby reducing the reflection of incident light, thereby improving the short-circuit current interruption of the battery, and further improving the photoelectric conversion efficiency of the battery. After the first side of the substrate 1 is texturized, the film layers formed on the first side have the same velvet structure as the first side.

[0038] As a specific example, the substrate 1 is put into a texturing liquid for texturing. The mass ratio of the components in the texturing liquid is H2O:KOH:additive=354:5.5:2, and the main components of the additive include: surfactant, nucleating agent, dispersant, catalyst and defoaming agent. The texturing temperature is 80°C and the texturing time is 400 seconds.

[0039] S3. Doping is performed on the first side of the substrate 1 to form a doping layer 11 of the second doping type on the first side. For example, when the substrate 1 is N-type doped, the doping type of the doping layer 11 is P-type doping, thereby forming a PN junction. As a specific example, the N-type single crystal silicon substrate 1 is placed in a boron diffusion furnace tube for a boron diffusion process, and the process temperature of the boron diffusion is 900°C to 1100°C. Boron sources such as trimethyl borate, boron tribromide, and boron trichloride can be used for boron diffusion. In the process of forming the boron doping layer (i.e., the doping layer 11) on the first side, a BSG (borosilicate glass) layer will naturally form under the action of oxygen.

[0040] It should be noted that the present disclosure does not impose specific restrictions on the boron source, process temperature, diffusion depth, etc. of the boron diffusion or phosphorus diffusion process. Personnel in this field can design according to actual needs, and the above limitations are only some specific examples.

[0041] S4. Remove the boron diffusion layer that has expanded on the second side, while retaining the BSG layer on the first side.

[0042] S5. A tunneling oxide layer 2 and a doped polysilicon layer 3 are sequentially formed on the second side of the substrate 1. The tunneling oxide layer 2 can saturate the dangling bonds on the surface of the substrate 1, reduce the interface defect state density on the second side of the substrate 1, and thus reduce the recombination center on the second side of the substrate 1, thereby reducing the recombination rate of carriers, and ultimately increasing the open circuit voltage of the solar cell and improving the photoelectric conversion efficiency of the solar cell. The material of the tunneling oxide layer can be any one of silicon oxide, aluminum oxide, tantalum oxide, zirconium oxide, and titanium dioxide. The doping type of the polysilicon layer 3 is the same as the doping type of the substrate 1.

[0043] For example, the tunnel oxide layer 2 is formed by chemical vapor deposition.

[0044] For example, the polysilicon layer 3 can be formed by chemical vapor deposition. In addition, a single crystal silicon layer can be formed first, and then the doped polysilicon layer 3 can be formed by doping and high-temperature annealing. As a specific example, when chemical vapor deposition is used, raw material gas (such as SiCl4, SiHCl3 or SiH4), doping gas (such as PH3) and hydrogen can be introduced, and after chemical reaction, the doped polysilicon layer 3 is grown on the second side. Therefore, the polysilicon layer 3 is generally doped with hydrogen atoms, so that the polysilicon layer 3 also has a certain passivation effect.

[0045] For example, the thickness of the polysilicon layer 3 is 45 nm to 85 nm, preferably 50 nm to 80 nm.

[0046] S6, removing the polysilicon layer 3 disposed on the first side and edge of the substrate 1.

[0047] S7, forming a passivation layer 4 on a side of the doped layer 11 away from the substrate 1, forming a Figure 2A The structure shown.

[0048] As a specific example, the material of the passivation layer 4 is aluminum oxide, which is formed by plasma enhanced chemical vapor deposition. For example, a mixed gas of trimethylaluminum and oxygen or nitrogen oxide (i.e., a mixed gas of trimethylaluminum and oxygen, or a mixed gas of trimethylaluminum and nitrogen oxide) is introduced, and the reaction temperature is between 250° C. and 350° C., thereby forming a passivation layer 4 of aluminum oxide. The thickness of the passivation layer 4 is 4 nm to 6.5 nm, preferably 4.5 nm to 6 nm.

[0049] S8, forming a first anti-reflection layer 5 on the passivation layer 4, and forming a second anti-reflection layer 6 on the polysilicon layer 3, so as to form Figure 2B The first anti-reflection layer 5 and the second anti-reflection layer 6 can reflect the light entering the solar cell, so that more sunlight is absorbed by the solar cell, thereby improving the short-circuit current interruption of the cell and further improving the photoelectric conversion efficiency of the cell.

[0050] As a specific example, the material of the first anti-reflection layer 5 and the second anti-reflection layer 6 is silicon nitride, and is formed by plasma enhanced chemical vapor deposition. For example, a mixed gas of SiH4 and NH3 is introduced, and the reaction temperature is between 300° C. and 550° C., so as to form the first anti-reflection layer 5 and the second anti-reflection layer 6 of silicon nitride. The thickness of the first anti-reflection layer 5 and the second anti-reflection layer 6 are both 70nm to 100nm.

[0051] In some examples, the semiconductor structure manufactured by steps S1 to S8 can be used as a battery substrate for performing step S9 and subsequent steps.

[0052] S9, forming a first electrode 71, wherein the first electrode 71 forms an ohmic contact with the doping layer 11 after passing through the first anti-reflection layer 5 and the passivation layer 4.

[0053] In the examples of the present disclosure, FIG. 2C to FIG. 2E As shown, the process of forming the first electrode 71 is as follows:

[0054] S91, such as Figure 2C As shown, firstly, a first groove 10 is formed on the passivation layer 4 and / or the first anti-reflection layer 5, and the first groove 10 extends from the surface of the first anti-reflection layer 5 to the passivation layer 4 or the first anti-reflection layer 5. As a specific example, the first groove 10 extends from the surface of the first anti-reflection layer 5 to the passivation layer 4.

[0055] Specifically, laser etching is used to form a marking point on the first anti-reflection layer 5 and at a position corresponding to the first electrode 71, and the first anti-reflection layer 5 and part of the passivation layer 4 at the position corresponding to the first electrode 71 are etched away by laser (that is, the first groove 10 extends from the surface of the first anti-reflection layer 5 to the inside of the passivation layer 4), and a thinner passivation layer 4 (that is, the passivation layer 4 at the bottom of the first groove 10) is retained at the position corresponding to the first electrode 71, and the thickness is 1nm to 2.5nm, preferably 2nm. For example, the parameters of the laser for etching include: a wavelength of 355nm, a power of 5W, a pulse frequency of 1KHz to 40KHz, and a scanning speed of 30nm / s to 100mm / s. Of course, in other possible examples, the first groove 10 can also be formed by wet etching or dry etching.

[0056] S92, printing metal paste (such as Figure 2D As shown), the metal paste is then heated and sintered, so that the metal paste corrodes the passivation layer 4 at high temperature and forms an ohmic contact with the doping layer 11 (as shown Figure 2E The peak temperature of the heating sintering is 600°C to 700°C, which is 100°C to 150°C lower than the peak temperature of 750°C to 800°C in the known technology.

[0057] S93 , the metal paste is cooled to form a first electrode 71 .

[0058] By opening the first groove 10, the thickness of the passivation layer 4 corroded by the metal slurry during the heating and sintering process can be reduced, so as to ensure that when the sintering temperature is reduced, the metal slurry located in the first groove 10 can also corrode the remaining passivation layer 4, thereby forming a good ohmic contact with the doping layer 11, so as to maintain the filling factor of the battery. In addition, after the sintering temperature is reduced, the escape of hydrogen atoms doped in each film layer (such as the polysilicon layer 3, the passivation layer 4, the first anti-reflection layer 5 and the second anti-reflection layer 6) in the battery can be effectively reduced to maintain the passivation effect of each film layer, thereby improving the open circuit voltage of the battery; at the same time, after the sintering temperature is reduced, the degree of damage to the passivation layer 4 by the metal slurry is reduced, and the consistency of the corrosion thickness of the passivation layer 4 by the metal slurry in all directions is high, so that the contact site between the metal slurry and the doping layer 11 is more uniform, which helps to maintain the filling factor of the battery.

[0059] In some examples, the metal paste uses low-corrosive silver paste to control the rate at which the metal paste corrodes the passivation layer 4 and the doping layer 11, to prevent the metal paste from corroding and penetrating the doping layer 11 and contacting the substrate 1, and to reduce the damage of the silver paste to the passivation layer 4 in the lateral direction. The main components of the silver paste include silver powder, glass powder, organic carrier and inorganic additives. The corrosiveness of the silver paste can be effectively reduced by reducing the ratio of the glass powder. For example, the ratio of the silver paste by weight percentage is: 90% to 95% silver powder, 0.2% to 0.3% glass powder, 1% to 3% organic carrier and 0% to 1% inorganic additive. For example, glass powder includes SiO2, B2O3, TiO2 and PbO, organic carriers include organic solvents (such as alcohol ester, diethylene glycol butyl ether, etc.), organic resins (such as acrylic resin, hydroxyethyl cellulose, polyvinyl butyral resin) and additives (such as polyamide wax, hydrogenated castor oil, dimethyl silicone oil), inorganic additives include composite additives (such as silver oxide, silver silicate, silver borate, silver selenate one or more) and other additives (such as aluminum powder, lead powder, zinc powder, silicon-magnesium alloy powder, boron powder, silicon powder, boronized silicon powder, silicon nitride, boron nitride, aluminum boride, zinc oxide powder, bismuth oxide powder, silicon dioxide powder one or more).

[0060] In some examples, the process of forming the first electrode 71 further includes:

[0061] S94, laser-assisted sintering of the metal slurry. It should be noted that step S94 is performed after step S93.

[0062] As a specific example, a bias voltage of 10V to 40V is applied between the metal paste and the second anti-reflection layer 6, and a laser with a wavelength of 500nm to 1200nm and a power of 10% to 80% is used to scan the metal paste in a line scanning manner, with a scanning speed of 30nm / s to 100mm / s and a scanning time of 0.5s to 1s. Among them, the spot diameter of the laser is 50μm to 300μm, and the shape is square or circular, etc. The metal paste is heated by laser, and the heat of the metal paste is concentrated and the heat dissipation is fast, which will not cause a large temperature rise in the remaining film layers in the battery, and therefore will not cause the battery to lose open circuit voltage; and under the action of the bias, silver ions can be effectively adsorbed on the doping layer 11, thereby improving the ohmic contact effect between the metal paste and the doping layer 11, thereby improving the filling factor of the battery, and achieving the purpose of improving battery efficiency.

[0063] S10 , forming a second electrode 72 , wherein the second electrode 72 passes through the second anti-reflection layer 6 and forms an ohmic contact with the polysilicon layer 3 .

[0064] In the examples of the present disclosure, FIG. 2C to FIG. 2E As shown, the process of forming the second electrode 72 is as follows:

[0065] S101, a second groove 20 is formed on the second anti-reflection layer 6 or on the second anti-reflection layer 6 and the polysilicon layer 3, so that the second groove 20 extends from the surface of the second anti-reflection layer 6 to the inside of the second anti-reflection layer 6 or the second polysilicon layer 3 (such as Figure 2C shown).

[0066] As a specific example, laser etching is used to form a marking point on the second anti-reflection layer 6 and at a position corresponding to the second electrode 72, and the second anti-reflection layer 6 and part of the polysilicon layer 3 at the position corresponding to the second electrode 72 are etched away by laser (that is, the second groove 20 extends from the surface of the second anti-reflection layer 6 to the polysilicon layer 3), and a thinner layer of polysilicon layer 3 (that is, the polysilicon layer 3 at the bottom of the first groove 20) is retained at the position corresponding to the second electrode 72. The ratio of the thickness of the polysilicon layer area exposed by the second groove 20 to the thickness of the polysilicon layer 3 is 50% to 66%, and the depth of the second groove 20 in the polysilicon layer 3 is 15nm to 35nm, preferably 20nm to 30nm.

[0067] For example, the parameters of the laser used for etching include: wavelength of 355 nm, power of 5 W, pulse frequency of 1 KHz to 40 KHz, and scanning speed of 30 nm / s to 100 mm / s.

[0068] S102, printing metal paste (such as Figure 2DAs shown), the metal paste is then heated and sintered, wherein the heating and sintering specifically adopts heating and sintering to make the metal paste react with polysilicon to form a silicon-metal alloy, thereby improving the ohmic contact effect between the metal paste and the polysilicon layer 3, thereby improving the filling factor of the battery, and ultimately improving the efficiency of the battery. After heating and sintering, the bottom of the metal paste is located in the polysilicon layer 3 to avoid damaging the tunneling oxide layer 2 and reducing the open circuit voltage of the battery.

[0069] The peak temperature of the heating sintering is 600°C to 700°C, which is 100°C to 150°C lower than the peak temperature of 750°C to 800°C in the known technology.

[0070] S103 , the metal paste is cooled to form a second electrode 72 .

[0071] By opening the second groove 20, the thickness of the second anti-reflection layer 6 corroded by the metal slurry can be reduced during the heating and sintering process (when the second groove 20 extends from the surface of the second anti-reflection layer 6 to the polysilicon layer 3, the metal slurry does not need to corrode the second anti-reflection layer 6 along the thickness direction of the battery). In this way, even when the sintering temperature is lowered, it is possible to ensure that the metal slurry forms a good ohmic contact with the polysilicon layer 3.

[0072] In addition, as the sintering temperature decreases, the rate at which the metal slurry corrodes the polysilicon layer 3 will also decrease, which helps control the depth of the metal slurry corroding the polysilicon layer 3. Therefore, in the process of forming the polysilicon layer 3, the polysilicon layer 3 can be thinned to reduce the parasitic absorption of the battery. In the case where the polysilicon layer 3 is thin, the metal slurry is not easy to corrode and penetrate the polysilicon layer 3.

[0073] In addition, after the sintering temperature is reduced, the escape of hydrogen atoms doped in each film layer in the battery (such as the polysilicon layer 3, the passivation layer 4, the first anti-reflection layer 5 and the second anti-reflection layer 6) can be effectively reduced to maintain the passivation effect of each film layer, thereby improving the open circuit voltage of the battery.

[0074] In some examples, the metal paste uses a low-corrosive silver paste to control the rate at which the metal paste corrodes the second anti-reflection layer 6 and the polysilicon layer 3, thereby preventing the metal paste from corroding and penetrating the polysilicon layer 3 and damaging the tunnel oxide layer 2. The low-corrosive silver paste printed on the second anti-reflection layer 6 can have the same ratio as the low-corrosive silver paste printed on the first anti-reflection layer 5.

[0075] In some examples, the process of forming the second electrode 72 further includes:

[0076] S104, laser-assisted sintering of the metal slurry. After laser sintering of the metal slurry, the temperature of the metal slurry rises instantaneously, and the heat dissipation is fast, which will not cause a large temperature rise in the remaining film layers in the battery, and therefore will not cause the battery to lose open circuit voltage; and under the action of bias, silver ions can be effectively adsorbed on the polysilicon layer 3, thereby improving the ohmic contact effect between the metal slurry and the polysilicon layer 3, thereby improving the filling factor of the battery, and achieving the purpose of improving the battery efficiency.

[0077] It should be noted that step S104 is performed after step S103.

[0078] In some examples, heating and sintering of the metal paste printed on the first side and the second side of the substrate 1 can be performed in the same process step. After heating and sintering of the metal paste printed on the first side and the second side of the substrate 1, the cell can be subjected to light injection treatment.

[0079] In summary, the method for preparing a solar cell provided by the embodiment of the present disclosure has at least the following advantages:

[0080] (1) By lowering the temperature for heating and sintering the metal paste printed on the first side and / or the second side of the substrate 1, the escape of hydrogen atoms doped in each film layer (such as the polysilicon layer 3, the passivation layer 4, the first anti-reflection layer 5 and the second anti-reflection layer 6) in the battery can be effectively reduced to maintain the passivation effect of each film layer, thereby improving the open circuit voltage of the battery.

[0081] (2) By lowering the temperature for heating and sintering the metal paste printed on the first side of the substrate 1, the degree of damage to the passivation layer 4 caused by the metal paste can be reduced, which helps to improve the open circuit voltage of the battery; in addition, the corrosion thickness of the passivation layer 4 by the metal paste in all directions is more consistent, making the contact points between the metal paste and the doping layer 11 more uniform, which helps to maintain the fill factor of the battery.

[0082] (3) By opening the first groove 10, the thickness of the passivation layer 4 corroded by the metal paste during the heating and sintering process can be reduced. When the sintering temperature is lowered, the metal paste in the first groove 10 can also corrode the remaining passivation layer 4, thereby forming a good ohmic contact with the doping layer 11, thereby maintaining the fill factor of the battery.

[0083] (4) By opening the second groove 20, the thickness of the second anti-reflection layer 6 corroded by the metal slurry can be reduced during the heating and sintering process. When the sintering temperature is lowered, it can also be ensured that the metal slurry forms a good ohmic contact with the polysilicon layer 3, thereby maintaining the fill factor of the battery.

[0084] (5) By lowering the temperature for heating and sintering the metal paste printed on the second side of the substrate 1, the rate at which the metal paste corrodes the polysilicon layer 3 is reduced, which helps to control the depth of the metal paste corroding the polysilicon layer 3; therefore, in the process of forming the polysilicon layer 3, the polysilicon layer 3 can be thinned to reduce the parasitic absorption of the battery. When the polysilicon layer 3 is thin, the metal paste is not easy to corrode and penetrate the polysilicon layer 3.

[0085] (6) Printing a low-corrosive silver paste on the first side of the substrate 1 helps control the corrosion rate of the silver paste on the passivation layer 4 and reduces the possibility of the silver paste corroding through the passivation layer and contacting the substrate.

[0086] (7) Printing a low-corrosive silver paste on the second side of the substrate 1 helps control the rate at which the silver paste corrodes the polysilicon layer 3 and reduces the possibility of the silver paste corroding through the polysilicon layer 3 and damaging the tunnel oxide layer.

[0087] (8) After the metal paste is heated and sintered, laser-assisted sintering is used to improve the ohmic contact effect between the metal paste and the passivation layer 4 and / or the polysilicon layer 3 without causing the battery to lose open-circuit voltage, thereby improving the fill factor of the battery and achieving the purpose of improving the battery efficiency.

[0088] Embodiment 2

[0089] FIG. 3A to FIG. 3E A cross-sectional structure diagram of the second solar cell provided by the present disclosure during the preparation process; Figure 3F The cross-sectional structure diagram of the second solar cell provided by the present disclosure. The solar cell in this embodiment is specifically a TBC (TOPCon back contact) cell.

[0090] The method for preparing a solar cell provided by the embodiment of the present disclosure is specifically as follows:

[0091] S1. Provide a substrate 1. The substrate 1 has a first side surface and a second side surface opposite to the first side surface. The first side surface of the substrate 1 is a light-facing surface, and the second side surface of the substrate 11 is a backlight surface. The doping type of the substrate 1 can be P-type doping or N-type doping.

[0092] S2. Texturing the first side of the substrate 1 to reduce the reflection of incident light, thereby improving the short-circuit current interruption of the battery, and further improving the photoelectric conversion efficiency of the battery. After the first side of the substrate 1 is texturized, the film layers formed on the first side have the same texture structure as the first side.

[0093] The second side of the substrate 1 is also textured or polished.

[0094] S3, sequentially forming a passivation layer 4 and a first anti-reflection layer 5 on the first side of the substrate 1. For example, the method of forming the passivation layer 4 and the first anti-reflection layer 5 is the same as that in the first embodiment.

[0095] S4, forming a tunnel oxide layer 2 and an intrinsic polysilicon layer 3 on the second side of the substrate 1 in sequence, Figure 3A The material of the tunnel oxide layer 2 can be any one of silicon oxide, aluminum oxide, tantalum oxide, zirconium oxide and titanium dioxide.

[0096] For example, the tunnel oxide layer 2 and the intrinsic polysilicon layer 3 are formed by LPCVD (Low Pressure Chemical Vapor Deposition).

[0097] S5, such as Figure 3B As shown, doping is performed on the intrinsic polysilicon layer 3 to form a first polysilicon layer 31 of a first doping type and a second polysilicon layer 32 of a second doping type. An isolation region 33 is provided between the first polysilicon layer 31 and the second polysilicon layer 32 to ensure electrical insulation between the first polysilicon layer 31 and the second polysilicon layer 32.

[0098] S6, such as Figure 3C As shown, a second anti-reflection layer 6 is formed on the polysilicon layer 3. The second anti-reflection layer 6 can increase the passivation characteristics of the solar cell surface, and the second anti-reflection layer 6 can reflect sunlight incident on the solar cell, thereby increasing the light absorption efficiency.

[0099] In some examples, such as Figure 3D As shown, after forming the second anti-reflection layer 6, the polysilicon layer 3 in the isolation region 33 is removed by laser etching to ensure electrical insulation between the first polysilicon layer 31 and the second polysilicon layer.

[0100] In some examples, the semiconductor structure manufactured by steps S1 to S6 can be used as a battery substrate for performing step S7 and subsequent steps.

[0101] S7 , forming a first electrode 71 and a second electrode 72 insulated from each other. The first electrode 71 forms an ohmic contact with the first polysilicon layer 31 , and the second electrode 72 forms an ohmic contact with the second polysilicon layer 32 .

[0102] As a specific example, the process of forming the first electrode 71 and the second electrode 72 is as follows:

[0103] S71, such as Figure 3E As shown, a first groove 10 and a second groove 20 are formed on the second side of the substrate 1 .

[0104] As a specific example, the first groove 10 extends from the surface of the second anti-reflection layer 6 to the first polysilicon layer 31, and the second groove 20 extends from the surface of the second anti-reflection layer 6 to the second polysilicon layer 32. The depth of the first groove 10 in the first polysilicon layer 31 is 15nm to 35nm, preferably 20nm to 30nm. The depth of the second groove 20 in the second polysilicon layer 32 is 15nm to 35nm, preferably 20nm to 30nm.

[0105] Of course, in other possible implementations, the first groove 10 and the second groove 20 may also extend from the surface of the second anti-reflection layer 6 to the inside of the passivation layer 4 .

[0106] S72, printing metal paste in the first groove 10 and the second groove 20, and then heating and sintering the metal paste to make the metal paste react with the polysilicon layer 3 to form a silicon-metal alloy, thereby improving the ohmic contact effect between the metal paste and the polysilicon layer 3, thereby improving the fill factor of the battery and ultimately improving the efficiency of the battery.

[0107] The peak temperature of the heating sintering is 600°C to 700°C, which is 100°C to 150°C lower than the peak temperature of 750°C to 800°C in the known technology.

[0108] S73, after the metal slurry is cooled, a first electrode 71 and a second electrode 72 are formed (eg Figure 3F shown).

[0109] In some examples, the metal paste uses low-corrosive silver paste to control the rate at which the metal paste corrodes the second anti-reflection layer 6 and the polysilicon layer 3 , thereby preventing the metal paste from corroding and penetrating the polysilicon layer 33 and damaging the tunnel oxide layer 2 .

[0110] In some examples, the process of forming the first electrode 71 and the second electrode 72 further includes:

[0111] S74, laser-assisted sintering of the metal slurry. After laser sintering of the metal slurry, the temperature of the metal slurry rises instantaneously, and the heat dissipation is fast, which will not cause a large temperature rise in the remaining film layers in the battery, and therefore will not cause the battery to lose open circuit voltage; and under the action of bias, silver ions can be effectively adsorbed on the polysilicon layer 3, thereby improving the ohmic contact effect between the metal slurry and the polysilicon layer 3, thereby improving the filling factor of the battery, and achieving the purpose of improving battery efficiency.

[0112] It should be noted that step S74 is performed after step S73.

[0113] The present disclosure also provides a solar cell, which is manufactured using the manufacturing method of Example 1 or Example 2.

[0114] There are a few points to note:

[0115] (1) The drawings of the embodiments of the present disclosure only relate to the structures related to the embodiments of the present disclosure, and other structures may refer to the general design.

[0116] (2) For the sake of clarity, in the drawings used to describe the embodiments of the present disclosure, the thickness of layers or regions is enlarged or reduced, that is, these drawings are not drawn according to the actual scale.

[0117] (3) In the absence of conflict, the embodiments of the present disclosure and the features therein may be combined with each other to obtain new embodiments.

[0118] So far, the technical solutions of the present disclosure have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present disclosure is obviously not limited to these specific embodiments. Without departing from the principles of the present disclosure, those skilled in the art may make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present disclosure.

Claims

1. A method for preparing a solar cell, characterized in that: include: Providing a battery substrate, the battery substrate comprising a substrate and a tunneling oxide layer, a polysilicon layer and a second anti-reflection layer sequentially formed on a second side of the substrate; A groove is formed on the second side of the battery substrate, wherein the groove extends from the surface of the second anti-reflection layer to the inside of the second anti-reflection layer or the polysilicon layer; printing metal paste in the groove; The metal paste is heated and sintered, so that the metal paste forms an ohmic contact with the polysilicon layer and the bottom of the metal paste is located in the polysilicon layer.

2. The method for preparing a solar cell according to claim 1, characterized in that: The groove extends into the polysilicon layer, and a ratio of a thickness of the polysilicon layer region exposed by the groove to a thickness of the polysilicon layer is 50% to 66%.

3. The method for preparing a solar cell according to claim 2, characterized in that: The depth of the groove in the polysilicon layer is 15 nm to 35 nm; and / or, The thickness of the polysilicon layer is 45 nm to 85 nm.

4. The method for preparing a solar cell according to claim 1, characterized in that: The peak temperature of the heating sintering is 600°C to 700°C.

5. The method for preparing a solar cell according to claim 1, characterized in that: The metal paste is silver paste, and the proportion of the silver paste by weight percentage is: 90% to 95% silver powder, 0.2% to 0.3% glass powder, 1% to 3% organic carrier and 0% to 1% inorganic additive.

6. The method for preparing a solar cell according to claim 1, characterized in that: After the metal slurry is heated and sintered, the metal slurry is subjected to laser-assisted sintering.

7. The method for preparing a solar cell according to claim 6, characterized in that: The laser assisted sintering comprises: applying a bias voltage of 10V to 40V between the metal paste and the first side of the substrate; The wavelength of the scanning laser is 500nm to 1200nm, the scanning speed is 1000m / s to 70000m / s, and the scanning time is 0.5s to 1s.

8. The method for preparing a solar cell according to claim 1, characterized in that: A doping layer, a passivation layer and a first anti-reflection layer are sequentially formed on the first side of the substrate.

9. The method for preparing a solar cell according to claim 1, characterized in that: The polysilicon layer includes a first polysilicon layer of a first doping type and a second polysilicon layer of a second doping type, and the grooves are formed in regions corresponding to the first polysilicon layer and the second polysilicon layer.

10. The method for preparing a solar cell according to any one of claims 1 to 9, characterized in that: The groove is formed by laser etching; or, The groove is formed by wet etching or dry etching.

11. A solar cell, characterized in that: The method is as described in any one of claims 1 to 10.

Citation Information

Cited By

  • Solar cell and preparation method thereof, laminated cell and photovoltaic module

    CN120456670A